2012
DOI: 10.1017/s0960258512000037
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and ecology of very fast germination

Abstract: A group of flowering plant species is known to germinate in less than 24 h from imbibition, but this phenomenon is often overlooked in the current literature. Here, I review this topic by searching the literature published since 1967 and listing the 28 most detailed cases found. Of these, 20 are species of Amaranthaceae (all formerly treated as Chenopodiaceae); 15 of these are from the subfamily Salsoloideae, which is characterized by the possession of spiral embryos. The non-chenopods listed are small numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 39 publications
2
60
1
1
Order By: Relevance
“…colubrina seeds presented fast germination (nearly 18 hours) and the absence of stage II might be view as an adaptive strategy in colonizing environments. Some authors, as Parsons (2012) report that fast germination species (until 24 h) present thin and permeable integument, which imbibe water promptly, allowing better utilization of temporarily favorable conditions, as is the case of A. colubrina seeds.…”
Section: Imbibition Curve and Imbibition And Desiccation Tolerance Lossmentioning
confidence: 99%
“…colubrina seeds presented fast germination (nearly 18 hours) and the absence of stage II might be view as an adaptive strategy in colonizing environments. Some authors, as Parsons (2012) report that fast germination species (until 24 h) present thin and permeable integument, which imbibe water promptly, allowing better utilization of temporarily favorable conditions, as is the case of A. colubrina seeds.…”
Section: Imbibition Curve and Imbibition And Desiccation Tolerance Lossmentioning
confidence: 99%
“…A similar pattern of significant differences between the two experiments is found in seeds treated with red light but only in lag of germination. Nevertheless in the two experiments, regardless of light treatment seeds began germinating in less than an estimated 14 hours from the start of imbibition, which qualifies 'Seaton Park' as a very fast germinating cultivar (Parsons, 2012).…”
Section: Comparison Between Dry and Imbibed Seeds Experimentsmentioning
confidence: 84%
“…Species with this trait, which evolved independently many times during angiosperm evolution, frequently have small to very small seeds with little or no endosperm or perisperm and thin membranous seed coats that imbibe rapidly (Parsons, 2012;Parsons et al, 2014). However 'Seaton Park' only partially fits in these characteristics.…”
Section: Comparison Between Dry and Imbibed Seeds Experimentsmentioning
confidence: 99%
“…Parsons (2012) reported 20 species of the family Amaranthaceae that have very fast germination rate. He indicated that the embryo cells of the seeds of these species elongate and the spiral embryo uncoils and ruptures within 10 minutes after imbibition.…”
Section: Discussionmentioning
confidence: 99%